The precious child - the fourth dimension of assessment A theoretical framework for evaluation - Arató, Ferenc (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The concept of formative assessment drew attention again to the issues of evaluation in the fi eld of education sciences. In the past decades the evidences of the discourse, which are often persuasive, sometimes controversial, obviously show that theoretical clarifi cation is needed for both researchers and teachers in practice. The aim of this article is to outline a theoretical framework by which someone can synchronize the different interpretations and research evidences of evaluation and assessment. The different dimensions of learning, explored by altering theories of learning, may form a basis for this theoretical clarifi cation. Four dimensions of both learning and assessment are differentiated in this proposal. Following these dimensions of assessment in this theoretical framework of evaluation, our aim is to launch a consensual dialogue about evaluation in the fi elds of research, everyday practice, and teacher education.